A Distinct Intestinal Domination Fingerprint in Patients Undergoing Allo-HSCT: Dynamics, Predictors and Implications on Clinical Outcomes - Ferreira Junior, Alexandre Soares [UNESP]; Alvarez, Danielle Amanda Niz [UNESP]; Souza, Larissa da Silva [UNESP]; Silva, Nathalia Linares [UNESP]; Machado, Luiza Dias [UNESP]; Hirai, Welinton Yoshio; Ciconelli, Rozana Mesquita; Feliciano, Joao Victor Piccolo; Colturato, Iago; Maurício Navarro Barros, George; Scheinberg, Phillip; Chao, Nelson Jen An.; et al. (MDPI, 2025)
Background: Although Enterococcus domination has been extensively evaluated in the context of allogeneic hematopoietic stem cell transplantation (allo-HSCT), the prevalence and clinical implications of other dominant genera remain poorly understood. Objective: In this study, we sought to determine the dynamics, predictors and clinical implications of intestinal domination in Brazilian patients undergoing allo-HSCT. Methods: In a prospective study of four Brazilian centers, fecal specimens were collected longitudinally prior to allo-HSCT until six months post-transplantation. To identify intestinal domination, we performed 16S rRNA gene sequencing using the Illumina platform. We then evaluated the impact of intestinal domination on overall survival and acute Graft-versus-Host-Disease (aGvHD) incidence. Finally, to identify predictors of intestinal domination, we performed a logistic regression model. Results: A total of 192 fecal specimens were collected from 69 patients. No significant changes in alpha or beta diversity were observed over the course of allo-HSCT. Among the 192 specimens, 131 (68%) presented intestinal domination. The top four dominant genera were Bacteroides, Akkermansia, Phascolarctobacterium, and Escherichia-Shigella. No significant associations were found between domination by these genera and either overall survival or aGvHD incidence. Furthermore, no patient-level characteristics, including age, sex, underlying disease, conditioning regimen, or stem cell source, reliably predicted intestinal domination. Conclusions: Our findings reveal a unique intestinal domination fingerprint in Brazilian patients and highlight the importance of geographic context in interpreting microbiota–outcome associations in allo-HSCT settings.